The house bunny [videorecording (Blu-Ray)] - Covert, Allen, 1964-; Giarraputo, Jack; Parry, Heather; Sandler, Adam; Lutz, Karen McCullah; Smith, Kirsten; Wolf, Fred; Faris, Anna, 1976-; Hanks, Colin, 1977-; Stone, Emma, 1988-; Dennings, Kat, 1986-; McPhee, Katharine, 1984-; et al. (Sony Pictures Home Entertainment, 2008)
When Playboy Bunny, Shelly, is tossed out of the Playboy Mansion, she has nowhere to go. She quickly falls in with the sorority girls from Zeta Alpha Zeta. The members of the sorority, all seven of whom are socially inept, are about to lose their house. The girls need a dose of what only the eternally bubbly Shelley can provide. Eventually, the girls, and Shelly, learn to stop pretending to be what they think others want them to be and start being themselves.